Implementasi Metode Perhitungan Aktuaria Program Dana Pensiun Menggunakan Flask - Muthia Dishanur Izzati; Mujiati Dwi Kartikasari (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
The pension fund program is a program that seeks future planning by providing pension benefits to participants. The vital thing that becomes a concern in the pension fund program is the actuarial cost method. There are two categories for actuarial cost methods, which are Accrued Benefit-Cost Method and Projected Benefit-Cost Method. The normal contribution characteristic of the Projected Benefit-Cost Method is more stable than the Accrued Benefit-Cost Method, so it is better to use it from the participants’ perspective. This study discusses the use of the Projected Benefit-Cost Method by calculating normal contributions and actuarial liabilities from the methods included in it, which are Attained Age Normal, Entry Age Normal, and Individual Level Premium. Based on the calculation results, the Entry Age Normal and Individual Level Premium methods have a smaller final value of normal contribution payments and have a larger actuarial liability than the Attained Age Normal. Thus, of the three methods included in the Projected Benefit-Cost Method, the Entry Age Normal and Individual Level Premium methods are better used from the perspective of participants. For the calculation of pension funding using the Attained Age Normal, Entry Age Normal, and Individual Level Premium methods to be widely implemented by the public, this study created an application website using flask, which can be accessed at https://perhitunganaktuariadapen.herokuapp.com/.